Product life-cycle considerations and the nature of strategic activities in entrepreneurial firms - Robinson, Richard B.; Pearce, John A. (Journal of Business Venturing, 1986)
This article reports on the nature of strategic activities and concerns reported by the CEOs of 77 entrepreneurial manufacturing firms once initial success in their marketplace had been achieved. Once the entrepreneurial firm achieves initial market success, the rate and number of strategic decisions faced by the entrepreneurs rapidly expand. A product becomes a product line. Product lines are added. Facilities and equipment are expanded. Personnel are added. A more formal and interpersonally complex organization becomes necessary. Markets and distribution channels expand, adding uncertainty to key market-related decisions. New financial risks arise, often as the result of undercapitalized cash flows. All of these factors combine to dramatically increase the pressure on the entrepreneur's strategic decision making. A major factor underlying the complicity inherent in this scenario is the product/market life cycle: the entrepreneurs must now organize and make decisions regarding several product lines that span several life-cycle stages with different strategic concerns, rather than regarding the narrow product range and limited life-cycle position that provided their initial success. The research reported in this article examined the relative importance of ten strategic activities and concerns reported by the 77 CEOs across products at different life-cycle stages. Initial interviews with selected CEOs and a review of the strategic-management literature identified ten key factors shaping the firm's evolving decision-making practices. These ten factors were divided into three groups: 1.1. Operational concerns that necessitate strategic attention: 1) changes in product design; 2) changes in process design; 3) risk of producing a product; and 4) emphasis on creativity.2.2. Dimensions influencing a firm's strategic-management activities: 5) demand on the strategic manager's time: 6) speed of decision making; 7) problems of internal politics; and 8) environmental uncertainty.3.3. Fundamental assumptions underlying a firm's decision-making practices: 9) annual-profit potential; and 10) value of strategic planning. There are two main sets of results: First, four process-related factors (value of strategic planning, demand on CEO's time, speed of decision making and annual-profit potential) were consistently the most important factors affecting performance within eact stage. Regardless of the life cycle of a particular product line, the manner or process by which decisions were made (strategic planning, CEO's time, and speed of decision making) and one key assumption or objective-annual-profit potential-were seen as factors more important in affecting performance than were operating concerns that necessitated strategic attention. Second, strategic issues associated with product lines at the development and growth stages of their life cycle are reported to be significantly more important to CEOs in entrepreneurial manufacturing firms than are strategic issues associated with mature or declining products lines. These results suggest that CEOs in entrepreneurial manufacturing firms should re-examine their strategies and practices to be sure that sufficient “strategic attention” is being given to decisions regarding mature product lines. In addition, these CEO's need to ensure, in the face of constant demands for their time and decisions, that operating concerns requiring strategic attention get appropriate consideration.